Perancangan Sistem Informasi Manajemen Proyek Pada Apada Studio Berbasis Web Menggunakan Metode Prototype - Kencana, I Made Adi Wira Surya (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Advances in information technology have changed the way companies operate, including in the architecture industry, one of which is Apada Studio. Currently, Apada Studio's project and financial recording process and project progress reporting are still done manually, which causes the data search process to be more complicated, time-consuming and potentially inaccurate project data. With the proposed “Design of a Web-Based Project Management Information System at Apada Studio Using the PrototypeMethod”, it is hoped that it can help Apada Studio in managing its projects better, improve performance and productivity, and reduce confusion and complexity in project management. This system design is designed using the prototype method and goes through various design stages, such as Unified Modeling Language (UML), Entity Relationalship Diagram (ERD), Flowmap, making Low Fidelity and High Fidelity designs using figma software. The results of the system design have been tested using the System Usability Scale (SUS) method with an average SUS score of 89.375 which shows the category “Excellent”, Grade B, and Acceptable. Testing is also done with Maze to assess the success and ease of users in completing tasks.